Research on a very energy-efficient and low-delay flooding algorithm for wireless sensor network - LI Fang-min1; LIU Xin-hua1; KUANG Hai-lan2 (Tongxin xuebao)
A novel flooding algorithm called priority covering algorithm was proposed for wireless sensor network.In the algorithm,a method of priority covering was used for assigning different forwarding priorities to vicinity nodes so as to make the flooding packet cover the whole network rapidly;a scheme of restrained forwarding and a scheme of dynamic delay for forwarding were used for restraining the redundant flooding packets and reducing the conflicting retransmission overhead.The result of simulation shows that the algorithm is more energy-efficient and low-delay than those similar flooding algorithms proposed.